Direct strip casting of metals and alloys : processing, microstructure and properties - Ferry, Michael (Woodhead Publishing in materials., 2006)
Direct strip casting is a continuous casting process for producing metallic sheet directly from the molten state that minimises the need for substantial secondary processing. This important book is the first to review the implications of strip casting technology for a range of alloys, including carbon and stainless steel, aluminium, magnesium, titanium, copper and other non-ferrous alloys. The book is divided into six chapters, with the first two describing the physical metallurgy of candidate alloys for direct strip casting and the development of microstructure during solidification. Chapter 3 describes the principles of continuous casting processes and the evolution of direct strip casting. It provides the foundation for the following two chapters which describe process variables and their impact on microstructure and strip quality. The final chapter describes possible techniques in secondary processing and fabrication of the as-cast strip. Two appendices discuss simulation and modelling issues, and the measurement and representation of textures in metal strip. Direct strip casting of metals and alloys is a standard reference on a technology destined to have a profound impact on the manufacturing landscape of the twenty-first century. First book to review the implications of strip technology for a range of alloysEssential book on a technology destined to have a profound impact on the manufacturing landscape of the twenty-first century.